1993
DOI: 10.1159/000113827
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Projections to the Anterior Telencephalon in the Budgerigar <i>(Melopsittacus undulatus)</i>

Abstract: The connections of a higher order auditory area in the neostriatum intermedium pars ventrolateralis (NTVL) were mapped with pathway tracing techniques in order to elucidate possible pathways by which auditory feedback may influence vocal learning in the budgerigar (Melopsittacus undulatus). Previous research has shown that NTVL receives projections from Field 'L' as well as adjacent portions of the dorsolateral neostriatum intermedium (NIDL) and hyperstriatum ventrale (HV) and, therefore, may be homologous to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
52
1

Year Published

1996
1996
2002
2002

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 11 publications
5
52
1
Order By: Relevance
“…The second band of Zenk+-labeled cells lies dorsal and ventral to the L2b nucleus. The most lateral band of Zenk+ neurons includes the NIVL (neostriatum intermedium pars ventrolateralis), a higher-order auditory region (Brauth and McHale 1988;Brauth et al 1994) that receives input from Field L and provides input to the HV medial to HVo (Hall et al 1993;Brauth et al 2001) (see Discussion).…”
Section: Zenk In Budgerigar Auditory Pathwaysmentioning
confidence: 99%
See 4 more Smart Citations
“…The second band of Zenk+-labeled cells lies dorsal and ventral to the L2b nucleus. The most lateral band of Zenk+ neurons includes the NIVL (neostriatum intermedium pars ventrolateralis), a higher-order auditory region (Brauth and McHale 1988;Brauth et al 1994) that receives input from Field L and provides input to the HV medial to HVo (Hall et al 1993;Brauth et al 2001) (see Discussion).…”
Section: Zenk In Budgerigar Auditory Pathwaysmentioning
confidence: 99%
“…Pathway tracing experiments (Brauth et al , 1994Brauth and McHale 1988) have shown that the L1-L2a-L3 complex is associated with auditory input relayed from the primary auditory thalamic nucleus, nucleus ovoidalis, to L2a (Hall et al 1993;Brauth et al 2001). The fields located dorsal and ventral to L2a (i.e., L1 and L3), which extend into the overlying and underlying neostriatum are functionally related to this system in birds (Wild et al 1993).…”
Section: Zenk In Budgerigar Auditory Pathwaysmentioning
confidence: 99%
See 3 more Smart Citations